The application of Form School Feng Shui model in a sleep environment: human preferences and subjective sleep quality evaluation - Hong, W.T.; Abdul-Rahman, H.; Wang, C. (Taylor & Francis, 2016)
Humans spend one-third of their lives in the sleep environment; however, research on how its interior arrangement affects individuals’ preferences and perceptions of sleep quality has not been emphasised. We predict that the Form School Feng Shui model corresponds to a mother’s embrace, which may fit most users’ desired paradigm in a sleep environment, and is, thus, probably supportive to better sleep quality. This paper investigates whether the desirable bedroom layout for humans corresponds to the Form School Feng Shui model, and whether the embraced arrangement in a sleep environment can enhance individual sleep quality. A nationwide questionnaire survey was conducted to investigate the perceptions of adults from multiple backgrounds, with a response rate of 27.0% (N = 405). The results showed the bedroom layout that was designed based on the Form School Feng Shui model was indicated as highly preferred but had no significant implications for better sleep quality. The findings supported the claim that the Form School Feng Shui model is broadly preferred for its application in the sleep environment; however, the hypothesis that such a model will contribute to better sleep quality is not established.